Ten new species of Daidalotarsonemus (Prostigmata: Tarsonemidae) from Costa Rica - Rezende, Jose M. [UNESP] (2015)
Ten new tarsonemid species of the genus Daidalotarsonemus found on native plants in Costa Rica are described herein: Daidalotarsonemus alas sp. n. Ochoa, Rezende & Lofego; Daidalotarsonemus azofeifai sp. n. Ochoa, Rezende & Lofego; Daidalotarsonemus bauchani sp. n. Rezende, Ochoa & Lofego; Daidalotarsonemus cuadradus sp. n. Ochoa, Rezende & Lofego; Daidalotarsonemus ginae sp. n. Ochoa, Rezende & Lofego; Daidalotarsonemus lini sp. n. Ochoa, Rezende & Lofego; Daidalotarsonemus marini sp. n. Ochoa, Rezende & Lofego; Daidalotarsonemus maryae sp. n. Ochoa, Rezende & Lofego; Daidalotarsonemus puntarenensis sp. n. Rezende, Ochoa & Lofego; and Daidalotarsonemus serratus sp. n. Rezende, Ochoa & Lofego. Measurements, a diagnosis for all the new species and a key to the species known to occur in Costa Rica is provided. The findings related in this article emphasize the importance of conducting mite surveys in rainforests around the world, to better understand the mite diversity which inhabits these biomes.http://zoobank.org/urn:lsid:zoobank.org:pub:8DF0990A-E78B-43A4-935E-389AE2DFC497